Divine presence amid violence: contextualizing the Book of Joshua - Brueggemann, Walter (Cascade Books, 2009)
The text of Joshua 11 -- Revelation, interpretation, and method -- Discerning revelation from God -- Divine permit -- Revelation in ancient context -- Revelation and canonical reading -- Yahweh versus horse and chariot -- Despite chariots of iron.